Natural amino acid salt catalyzed aldol reactions of isatins with ketones: highly enantioselective construction of 3-alkyl-3-hydroxyindolin-2-ones. Issue 17 (15th September 2015) - Chen, Gong; Ju, Yuan; Yang, Tao; Li, Zicheng; Ang, Wei; Sang, Zitai; Liu, Jie; Luo, Youfu
Graphical abstract